Association of Alopecia Areata with other Autoimmune Diseases: A Cross- Sectional Study in Western Nepal - Basnet, Binamra; Jwarchan, Jayanti; Silwal, Mrinal; Khadga, Shreyesha; Kumar, Ajay (Nepal Journal of Medical Sciences, 2024)
Introduction: Alopecia areata (AA) is a common chronic inflammatory disease that causes nonscarring hair loss. The severity ranges from small patches of hair loss which usually recover spontaneously, to complete alopecia where the prognosis for hair regrowth is poor.[1] AA has affected approximately 2% of the general population [2,3]. The estimated lifetime risk in the general population is 2%. [4] The prevalence rate of AA is around 0.1 to 0.2%.[5] Methods: A single centered, hospital based, prospective cross-sectional analytical study was conducted in the Department of Dermatology of Manipal Teaching Hospital. The study was conducted from July 2023 to December 2023 after the permission of Institutional Research Committee (Reference ID: MCOMS/IRC/575/GA) and obtaining written and informed consent from the patients. We recruited 39 patients with diagnosis of alopecia areata who presented to the Department of Dermatology during the study period. Sampling was done by nonprobability convenience method. Data were applied with appropriate statistical tests, results with p value <0.05 were considered significant. Results: There was a total of 39 patients of which 56.4% (22) were females and 43.6% (17) were males. The patient's ages ranged from 8 years to 65 years with mean age being 32.49 ± 13.51years. Patients were classified according to the severity of the disease. Among 39 patients, 30 (76.8%) had mild disease, seven (17.9%) had moderate and two (5.1%) of them had severe disease. In our study we could not find statistically significant association between alopecia areata and other autoimmune diseases such as diabetes mellitus, thyroid abnormality, vitiligo and atopy. Conclusions: In this study there was no significant association between alopecia areata and other autoimmune disorders like diabetes mellitus, thyroid dysfunction, anaemia, atopy and vitiligo. The lack of significant association in our study doesn't exclude the importance of screening of these diseases in a patient with alopecia areata.